New butenolide cinnamate and other biological active chemical constituents from Polygonum glabrum - Said, Madhukar S.; Chinchansure, Ashish A.; Nawale, Laxman; Durge, Ankita; Wadhwani, Ashish; Kulkarni, Smita S.; Sarkar, Dhiman; Joshi, Swati P. (Natural Product Research, 2015)
Phytochemical investigation of the methanol extract of the aerial parts of Polygonum glabrum afforded one new natural product (-)-2-methoxy-2-butenolide-3-cinnamate (1) along with six known compounds, -hydroxyfriedalanol (2), 3-hydroxy-5-methoxystilbene (3), (-) pinocembrin (4), sitosterol-(6-O-palmitoyl)-3-O–d-glucopyranoside (5), (-) pinocembrin-5-methyl ether (6) and sitosterol-3-O–d-glucopyranoside (7). Compound 1 showed promising in vitro anti-HIV-1 activity against primary isolates HIV-1(UG070) (X4, subtype D) and HIV-1(VB59) (R5, subtype C) assayed using TZM-bl cell line with IC50 in the range of 15.68-22.43g/mL. The extract showed TI in the range of 19.19-27.37 with IC50 in the range of 10.90-15.55g/mL. Compounds 1, 3 and 4 exhibited in vitro anti-mycobacterium activity against Mycobacterium tuberculosis H37Ra with IC50 values of 1.43, 3.33 and 1.11g/mL in dormant phase and 2.27, 3.33 and 1.21g/mL in active phase, respectively. Compound 4 was found to be the most active antiproliferative with IC50 values of 1.88-11.00g/mL against THP-1, A549, Panc-1, HeLa and MCF7 cell lines.
Keywords: anti-HIV-1; anti-mycobacterium; antiproliferative; phytochemicals; Polygonaceae; Polygonum glabrum

Acetone and methanol fruit extracts of terminalia paniculata inhibit HIV-1 infection in vitro - Durge, Ankita; Jadaun, Pratiksha; Wadhwani, Ashish; Chinchansure, Ashish A.; Said, Madhukar; Thulasiram, H. V.; Joshi, Swati P.; Kulkarni, Smita S. (Natural Product Research, 2017)
In this study, we report the in vitro anti-HIV1 activity of acetone and methanol extracts of fruit of Terminalia paniculata. Cytotoxicity tests were conducted on TZM-bl cells and peripheral blood mononuclear cells (PBMC), the CC50 values of both the extracts were 260g/mL. Using TZM-bl cells, the extracts were tested for their ability to inhibit replication of two primary isolates HIV-1 (X4, Subtype D) and HIV-1 (R5, Subtype C). The activity against HIV-1 primary isolate (R5, Subtype C) was confirmed using activated PBMC and by quantification of HIV-1 p24 antigen. Both the extracts showed anti-HIV1 activity in a dose-dependent manner. The EC50 values of the acetone and methanol extracts of T. paniculata were 10.3g/mL. The enzymatic assays were performed to determine the mechanism of action which indicated that the anti-HIV1 activity might be due to inhibition of reverse transcriptase (77.7% inhibition) and protease (69.9% inhibition) enzymes.